Patient-driven research: Initial results from a prospective health–related quality of life study performed at the request of patients living with hairy cell leukemia. (September 2022) - Anghelina, Mirela; Naughton, Michelle J.; Zhao, Qiuhong; Ruppert, Amy S.; Neal, Jasmine; Rogers, Kerry A.; Blachly, James S.; Lozanski, Gerard; Bhat, Seema A.; Kraut, Eric; Epperla, Narendranath; Mathur, Puneet; et al.
Abstract: A diagnosis of leukemia can have a profound effect on patients' health-related quality of life (HRQoL), however this has not been measured prospectively in patients with hairy cell leukemia (HCL). At the request of patients living with HCL who had identified this gap in knowledge about the disease, we conducted a longitudinal study of HRQoL among patients enrolled in the HCL Patient Data Registry (PDR). From September 1, 2018 to September 1, 2020, 165 patients were enrolled in the study and completed the baseline survey. The Functional Assessment of Cancer Therapy – Leukemia (FACT-Leu) was used to measure patients' HRQoL. Results show that newly diagnosed HCL patients reported the lowest HRQoL, followed by patients in relapse and those on "watch and wait." Factors associated with higher (better) FACT-Leu total scores in the multivariable analysis included older age, higher social support, and greater physical activity. These same factors were associated with lower levels of fatigue. In rare diseases where it is difficult to perform large prospective studies, patient/researcher collaborations are critical for the identification of studies that are of importance to patients and their families in order to maximize the benefits of the research and improve the lives of patients living with HCL. Highlights: HCL patients reported better health-related quality of life than patients with other chronic leukemias. Newly diagnosed patients had the poorest quality of life scores. The older the patient, the better their quality of life. Better quality of life and less fatigue were associated with increased physical activity and good social support. On average, 78% of patients indicated they were able to work while managing their disease.